Predictors of Balloon Guide Catheter Assistance Success in Stent-retrieval Thrombectomy for an Anterior Circulation Acute Ischemic Stroke - McCarthy, David J (Cureus, 2019)
Introduction Mechanical thrombectomy has become the standard treatment for large vessel occlusion (LVO) in acute ischemic stroke (AIS) in well-selected patients. Although many devices and strategies exist, the use of a balloon-tip guide catheter (BGC) with stent-retriever (SR) may hold several advantages. We aim to assess the efficacy and identify predictors of technical success of this unique approach. Methods From our prospectively maintained database, we identified consecutive cases in which a BGC was used for stent-retriever thrombectomy in anterior circulation LVO between 2015 and 2016. Baseline and procedural characteristics were captured and analyzed. Predictors of technical and clinical outcomes were identified by multivariable logistic regression analysis. Results Ninety-three patients with AIS-LVO were treated with BGC-assisted mechanical thrombectomy. The mean age was 71 years old (SD 14), with 49.5% male (n=46). Pre-operative IV-tPA was administered in 55.9% (n=52) of cases. The most common location of occlusive thrombus was M1 (64.5%, n=60). Successful recanalization (mTICI=2b-3) was achieved in 86.0% (n=80) of cases while complete revascularization (mTICI-3) was achieved in 56.5% (n=52). There was a first-pass success rate of 52.7% (n=49). At discharge, 38.7% of the patients were functionally independent (mRS≤2). Multivariate analysis revealed that the middle cerebral artery location was strongly predictive of first-pass success, resulting in mTICI =2b revascularization (OR 7.10, p=0.018). Additionally, female gender (OR 2.85, p=0.042) and decreasing mTICI were associated with a poor clinical outcome (mRS≥4; OR 1.76, p=0.008). Conclusions BGC assistance in stent retrieval thrombectomy is safe and effective for AIS due to anterior circulation LVO. Further investigation is required to elucidate the optimal treatment strategy based on patient and disease characteristics.